Microbiological and molecular characterization of Staphylococcus hominis isolates from blood. - Soraya Mendoza-Olazarán; Rayo Morfin-Otero; Eduardo Rodríguez-Noriega; Jorge Llaca-Díaz; Samantha Flores-Treviño; Gloria Ma González-González; Licet Villarreal-Treviño; Elvira Garza-González (PLoS ONE, 2013)
Background Among Coagulase-Negative Staphylococci (CoNS), Staphylococcus hominis represents the third most common organism recoverable from the blood of immunocompromised patients. The aim of this study was to characterize biofilm formation, antibiotic resistance, define the SCCmec (Staphylococcal Chromosomal Cassette mec) type, and genetic relatedness of clinical S. hominis isolates. Methodology S. hominis blood isolates (n = 21) were screened for biofilm formation using crystal violet staining. Methicillin resistance was evaluated using the cefoxitin disk test and the mecA gene was detected by PCR. Antibiotic resistance was determined by the broth microdilution method. Genetic relatedness was determined by pulsed-field gel electrophoresis (PFGE) and SCCmec typed by multiplex PCR using two different methodologies described for Staphylococcus aureus. Results Of the S. hominis isolates screened, 47.6% (10/21) were categorized as strong biofilm producers and 23.8% (5/21) as weak producers. Furthermore, 81% (17/21) of the isolates were methicillin resistant and mecA gene carriers. Resistance to ampicillin, erythromycin, and trimethoprim was observed in >70% of isolates screened. Each isolate showed a different PFGE macrorestriction pattern with similarity ranging between 0-95%. Among mecA-positive isolates, 14 (82%) harbored a non-typeable SCCmec type: eight isolates were not positive for any ccr complex; four contained the mec complex A ccrAB1 and ccrC, one isolate contained mec complex A, ccrAB4 and ccrC, and one isolate contained the mec complex A, ccrAB1, ccrAB4, and ccrC. Two isolates harbored the association: mec complex A and ccrAB1. Only one strain was typeable as SCCmec III. Conclusions The S. hominis isolates analyzed were variable biofilm producers had a high prevalence of methicillin resistance and resistance to other antibiotics, and high genetic diversity. The results of this study strongly suggested that S. hominis isolates harbor new SCCmec structural elements and might be reservoirs of ccrC1 in addition to ccrAB1 and mec complex A.